The structural modification and magnetism of many-layer epitaxial graphene implanted with low-energy light ions. (15th June 2022) - Mazza, Alessandro R.; Miettinen, Anna; Gai, Zheng; He, Xiaoqing; Charlton, Timothy R.; Ward, Thomas Z.; Conrad, Matthew; Bian, Guang; Conrad, Edward H.; Miceli, Paul F.
Abstract: Modifying the properties of graphene has gained wide interest for a plethora of potential applications, including spintronics. One approach has demonstrated that proton irradiation can induce ferromagnetism in graphene as well as in graphite. However, little is known about how the protons interact with graphene, the mechanism that creates the ferromagnetism, or whether the protons remain in the graphene. Here we report an investigation, broadly relevant to graphitic carbon, using low-energy (360–2000 eV) ions of hydrogen, deuterium, and helium implanted into multilayer epitaxial graphene. Complementary x-ray and neutron reflectivity demonstrate that essentially all of the implanted hydrogen remains chemisorbed in graphene. In situ x-ray diffraction reveals significantly different rates of interlayer expansion of the multilayer graphene. Analysis of these data demonstrates that the interlayer expansion arises entirely from the interstitials created by the ions and not from hydrogen that remains in the graphene. The results also establish a quantitative measure of the layer expansion due to carbon interstitials. Magnetometry and x-ray diffraction studies show that the magnetic moment relates to the amount of interstitial carbon rather than the amount of hydrogen, demonstrating that the induced room-temperature ferromagnetism arises directly from the disrupted bonding of the carbon lattice. Graphical abstract: Image 1